A Study of Thermodynamic Properties of Transition Metal Diborides - Pankaja Singh, A. Saud Khan and Mahendra Mehra, Tanveer Ahmad Wani* (Recent Research in Science and Technology, 2010)
Abstract The diborides are members of a broad class of materials known as the boron-rich solids, which consist of extended networks of covalently bonded boron (B) atoms stabilized through donation of electrons from the metal atoms. Although the structures of the diborides are unique, their physical properties are somewhat similar to those of nitrides and carbides; they are extremely hard and have very high melting points. They are attractive for the same types of applications as super hard, refractory materials, such as in composites and in hard coatings. The proposal presents an overview of some of the important properties of transition metal diborides (TMB2), as these are of interest for fundamental reasons as well as for practical applications. Keywords: TMB2; AlB2; Physical properties